Corrosion-resistant steel slag desert sand composite sand preparation process
Patent Information
- Application Number
- CN202611178889.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-23
AI Technical Summary
但目前单独将钢渣破碎、筛分作为骨料使用时,往往存在级配不连续、易发生体积安定性不良等问题
1、本申请以钢厂转炉钢渣为原料,有效消纳了大量钢铁工业固废,缓解了钢渣堆存带来的土地占用与环境污染问题;同时将塔克拉玛干沙漠砂转化为高价值工程材料,大幅减少了对天然河砂的开采需求,保护了河道生态环境。钢渣与沙漠砂的协同利用,实现了"以废治废、变废为宝"的双重环保目标。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the fields of solid waste resource utilization, building materials and environmental engineering materials, and in particular to a process for blending corrosion-resistant steel slag desert sand composite sand. Background Technology
[0002] Natural river sand, as an important building aggregate, has suffered from severe resource depletion and ecological environmental problems due to long-term, unregulated, and large-scale mining. Finding alternative sand sources has become an urgent need for the sustainable development of the construction industry. Regions such as the Taklamakan Desert possess abundant desert sand resources, which, if used in engineering construction, would bring enormous economic and environmental benefits. However, due to its naturally formed characteristics, desert sand suffers from extremely uneven gradation and low packing density, making it unsuitable for direct application and failing to meet the technical requirements of engineering materials such as concrete, thus restricting its large-scale application.
[0003] On the other hand, the large amount of steel slag generated during the steel industry is a significant industrial solid waste. Its long-term storage not only occupies land but also causes environmental pollution problems such as dust and heavy metal ion leaching. Using steel slag as aggregate in the building materials industry is one important way to utilize its resources. Steel slag itself has high hardness, good wear resistance, and certain chemical corrosion resistance. However, currently, when steel slag is crushed and screened alone for use as aggregate, problems such as discontinuous gradation and poor volume stability often occur.
[0004] In the existing technology, although there have been attempts to combine desert sand with other materials to improve its performance, or to use steel slag in building materials, the following shortcomings still exist: Patent application No. 201220544564.8 discloses a process for preparing permeable bricks using steel slag and desert sand, but its technical solution focuses on the vibration and pressure molding of specific permeable brick products, and does not involve the generalized blending process of the composite sand itself, and lacks precise control over the key indicators of the composite sand; while the composite sand concrete technology disclosed in patent application No. 202010602532.8 uses a combination of Gobi sand and desert sand, but does not contain steel slag components, so it cannot utilize the corrosion resistance of steel slag, nor can it achieve the resource utilization of solid waste.
[0005] Therefore, this invention proposes a process for blending corrosion-resistant steel slag desert sand composite sand. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a process for blending corrosion-resistant steel slag desert sand composite sand.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A process for preparing corrosion-resistant steel slag desert sand composite sand includes the following steps: Step S1, Raw material pretreatment: Steel slag and desert sand are pretreated separately; The pretreatment of steel slag includes: screening the steel slag raw material to ensure that it all passes through a 4.75mm sieve, followed by washing and drying. The pretreatment of desert sand includes: screening the desert sand raw material so that all of it passes through a 4.75mm sieve; Step S2, Volume ratio calculation: Based on the physical property parameters of steel slag and desert sand, calculate the volume mixing ratio of steel slag and desert sand required to make the fineness modulus of the final composite sand fall within the range of 2.3 to 3.0; Step S3, Mixing and blending: According to the volume ratio calculated in step S2, the pretreated steel slag and desert sand are dry and uniformly mixed to obtain the corrosion-resistant steel slag and desert sand composite sand. Step S4, Performance Testing: The composite sand obtained in Step S3 is sampled and tested according to national standards. The test indicators include fineness modulus, mud content, bulk density, alkali activity and corrosion resistance, ensuring that its fineness modulus is between 2.3 and 3.0 and that the other indicators meet the requirements for engineering sand.
[0008] As one technical solution of this application, the desert sand is Taklamakan Desert sand, with an apparent density of 2440 kg / m³. 3 The bulk density is 1530 kg / m³ 3 ; The particle size distribution characteristics are: cumulative residue on a 0.075 mm sieve greater than 95%, and cumulative residue on a 0.15 mm sieve greater than 80%. The apparent density of the steel slag is 3350 kg / m³. 3 The bulk density is 2170 kg / m³ 3 .
[0009] As a preferred technical solution of this application, after the steel slag is screened, its main particles are distributed in the range of 2.36 mm, 1.18 mm and 0.6 mm sieve apertures, and the particles that pass through the 4.75 mm sieve and whose particle size is distributed in the range of 1.18-4.75 mm account for the main mass.
[0010] As a preferred technical solution of this application, the volume ratio of steel slag to desert sand in step S2 is in the range of 1:1 to 1:3.
[0011] As a preferred technical solution of this application, the moisture content at the end of the drying in step S1 is less than 1%; the dry uniform mixing in step S3 adopts a forced mixer or a gravity-free mixer, and the mixing time is not less than 5 minutes.
[0012] As a preferred technical solution of this application, the steel slag is converter steel slag, whose main chemical composition includes CaO 40%-50%, SiO2 15%-20%, and Fe2O3 15%-25%. The steel slag is tested for free calcium oxide content before pretreatment to ensure that its volume stability meets the standard requirements for steel slag for construction.
[0013] As a technical solution of this application, a corrosion-resistant steel slag desert sand composite sand is prepared by the aforementioned blending process. Its fineness modulus is 2.3-3.0, and its particle size distribution meets the requirements of construction sand in Zone II of the national standard GB / T 14684. Moreover, its corrosion resistance is superior to that of pure desert sand.
[0014] As a preferred technical solution of this application, the mass loss rate of the composite sand in the sulfate erosion test is reduced by at least 40% compared with that of pure desert sand, and the sulfate erosion test adopts the Na2SO4 solution immersion method.
[0015] As a preferred technical solution of this application, the bulk density of the composite sand is greater than that of pure desert sand, and its mud content, alkali activity and harmful substance content all comply with the provisions of national standard GB / T 14684.
[0016] The beneficial effects of this invention are as follows: 1. This application utilizes steel slag from steel mill converters as raw material, effectively disposing of a large amount of solid waste from the steel industry and alleviating the land occupation and environmental pollution problems caused by steel slag stockpiling; at the same time, it transforms Taklamakan Desert sand into high-value engineering materials, significantly reducing the demand for natural river sand mining and protecting the river's ecological environment. The synergistic utilization of steel slag and desert sand achieves the dual environmental protection goals of "treating waste with waste and turning waste into treasure."
[0017] 2. By precisely adjusting the volume ratio of steel slag to desert sand, the fineness modulus of the composite sand was successfully and stably controlled within the optimal range for engineering sand. The gradation was continuous and met the requirements for medium sand in Zone II of the national standard, breaking through the technical bottleneck of poor gradation when using desert sand alone. The coarse particles of steel slag effectively filled the voids between the fine particles of desert sand, significantly improving the packing density of the composite sand and laying the foundation for reducing the amount of cementitious materials or increasing the strength of concrete in subsequent concrete preparation. Relying on the excellent chemical corrosion resistance of steel slag, the mass loss rate of the composite sand in the sulfate erosion environment of this invention is significantly lower than that of pure desert sand and ordinary manufactured sand. Moreover, the higher the steel slag content, the better the corrosion resistance. It is suitable for harsh engineering conditions such as saline soil areas, coastal high-humidity environments, and industrial buildings containing corrosive media. By strictly controlling the free calcium oxide content and autoclaving pulverization rate in steel slag, the volume stability of steel slag is ensured to meet the relevant standard requirements. 3. The process route only includes five steps: "screening → washing → drying → volume ratio metering → dry mixing," requiring no chemical additives or complex modification treatments. All equipment used is standard equipment in the building materials industry, with a short process flow, simple operation, low energy consumption, and easy industrialization and large-scale production. 4. The overall process is suitable for regions with both large steel enterprises and abundant desert sand resources, enabling localized resource utilization, significantly reducing raw material procurement and transportation costs, and powerfully promoting the development of regional circular economy; the product can be widely used in civil and industrial buildings, road base courses, slope protection projects, as well as structural engineering in harsh environments such as saline soil areas and coastal high humidity areas, with broad market prospects.
[0018] 5. In summary, this invention, through an integrated process of "pretreatment → volume ratio compounding → precise control of fineness modulus → corrosion resistance enhancement → stability control", transforms two low-quality resources, industrial solid waste steel slag and desert sand, into high-performance, corrosion-resistant standardized engineering sand at low cost without the need for chemical additives. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0020] I. Basic Raw Material Parameters All raw materials used in the embodiments and comparative examples of this invention are from the same batch: Taklamakan Desert sand: apparent density 2440 kg / m³, bulk density 1530 kg / m³. Sieving results are shown in Table 1.
[0021] Table 1 Desert Sand Sieving Grading
[0022] Steel slag from Bayi Steel Plant: apparent density 3350 kg / m³ 3 Bulk density 2170 kg / m³ 3 The screening results are shown in Table 2. The main chemical composition range of the converter steel slag used from Bayi Steel Plant is: CaO 40%-50%, SiO2 15%-20%, Fe2O3 15%-25%, and other components include MgO, Al2O3, MnO, P2O5, etc.
[0023] Table 2 Grading of 2-4mm Steel Slag Screen
[0024] II. Standards and Instruments for Experimental Testing Methods (1) Particle size distribution and fineness modulus testing Testing Standard: GB / T 14684-2022 "Construction Sand" Test method: Standard sieving method was used. Standard sieves were stacked in descending order of aperture size (4.75mm, 2.36mm, 1.18mm, 600μm, 300μm, 150μm, 75μm). The samples were dried in an oven at (105±5)℃ until constant weight (weighing at 1-hour intervals with a difference ≤0.1%). The mechanical sieving time was set to 10±1min. The mass of the residue on each sieve was weighed, and the individual sieve residue rate and cumulative sieve residue rate were calculated.
[0025] Formula for calculating fineness modulus:
[0026] Among them, A 4.75 A 2.36 A 1.18 A 0.6 A 0.3 A 0.15 These represent the cumulative percentage of residue on each sieve (%).
[0027] Main instruments and equipment: standard square hole sieves (4.75 mm, 2.36 mm, 1.18 mm, 0.6 mm, 0.3 mm, 0.15 mm, 0.075 mm), electric heating drying oven (temperature control accuracy ±1℃), vibrating sieve machine, electronic balance (accuracy 0.1g).
[0028] (2) Bulk density detection Testing Standard: GB / T 14684-2022 "Construction Sand" Test method: Volumetric cylinder method. Place the sample into a standard volumetric cylinder, level the surface with a ruler, weigh the total mass of the volumetric cylinder and the sample, subtract the mass of the volumetric cylinder to obtain the mass of the sample, and divide by the volumetric cylinder volume to obtain the bulk density.
[0029] Main instruments and equipment: measuring cylinder (1L or 10L capacity), electronic balance (accuracy 1g), ruler, drying oven.
[0030] (3) Mud content detection Testing standard: GB / T 14684-2022 "Construction Sand"; Test method: Water washing method (sieve washing method). Place the sample in a container and add water to wash it to separate the mud, powder and sand particles. Pass the turbid liquid through a 75μm sieve and wash it repeatedly until the water is clear. Dry the residue on the sieve and weigh it.
[0031] Main instruments and equipment: 75μm standard sieve, drying oven, electronic balance (accuracy 0.1g), containers.
[0032] (4) Test of sulfate corrosion resistance Testing standard: Refer to the sulfate attack resistance test method in GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete"; Test method: Na₂SO₄ solution immersion method was used. 500g of composite sand with a particle size of 0.15-4.75mm was immersed in 2L of 5% Na₂SO₄ solution. The solution temperature was controlled at (20±2)℃. The solution was changed every 7 days, and the immersion cycle was 28 days. The mass loss rate was calculated by measuring the mass change of the sample before and after immersion.
[0033] Main instruments and equipment: electronic balance (accuracy 0.01g), constant temperature and humidity test chamber, pH meter, drying oven.
[0034] (5) Detection of free calcium oxide content in steel slag Testing standard: YB / T 4328-2012 "Determination of Free Calcium Oxide Content in Steel Slag"; Detection method: Ethylene glycol-EDTA chemical titration method. The total free calcium content in steel slag is determined by ethylene glycol-EDTA chemical titration method, and the calcium hydroxide content is determined by thermogravimetric analysis. The difference between the two is the free calcium oxide content.
[0035] Main instruments and equipment: high temperature resistance furnace, thermogravimetric analyzer, burette, electronic balance (accuracy 0.0001g), magnetic stirrer.
[0036] (6) Test of volume stability of steel slag Testing standard: GB / T 24175 "Test Method for Stability of Steel Slag"; Testing methods: The volume stability of steel slag is reflected by the water immersion expansion rate or autoclaving pulverization rate. The autoclaving pulverization rate method is applicable to steel slag in building mortar, building materials, and concrete.
[0037] Main instruments and equipment: autoclave (working pressure ≥2.0MPa), drying oven, electronic balance (accuracy 0.1g), standard sieve.
[0038] III. Examples and Comparative Examples Example 1 A process for preparing corrosion-resistant steel slag desert sand composite sand includes the following steps: Step S1, Raw material pretreatment: Steel slag and desert sand are pretreated separately; The pretreatment of steel slag includes: taking converter steel slag produced by Xinjiang Bayi Steel Plant, screening it using a vibrating screen (screen size 4.75mm), taking the undersize material, and sending the undersize steel slag into a drum-type stone washing machine, rinsing it with clean water for 5-10 minutes to remove surface adhering substances; sending the washed steel slag into a dryer, drying it at 105℃±5℃ to constant weight (moisture content <1%), and setting it aside for later use.
[0039] The pretreatment of desert sand includes: taking Taklamakan desert sand, screening it through a 4.75mm square hole sieve to remove excessively large impurities, and obtaining pretreated desert sand; The free calcium oxide content in the steel slag was tested according to YB / T 4328-2012, and the result was 2.1%; the autoclaving pulverization rate of the steel slag was tested according to GB / T 24175, and the result was 1.8%, which meets the stability requirements for steel slag used in construction. Step S2, Volume ratio calculation: Based on the apparent density of desert sand 2440 kg / m³ 3 Bulk density 1530 kg / m³ 3 The apparent density of steel slag is 3350 kg / m³. 3 Bulk density 2170 kg / m³ 3 The volume ratio of steel slag to desert sand was determined to be 1:2. Step S3, Mixing and blending: Accurately weigh 500L of pretreated dried steel slag (approximately 1085kg) and 1000L of pretreated desert sand (approximately 1530kg), put them into a 2m³ capacity forced mixer, set the speed to medium-high speed, and continuously dry mix for 8 minutes until the color is uniform and there is no visible layering. Step S4, Performance Testing: The composite sand obtained in step S3 was sampled and tested according to national standards. The results are shown in Table 3.
[0040] Example 2 A process for preparing corrosion-resistant steel slag desert sand composite sand includes the following steps: Step S1, Raw material pretreatment: Steel slag and desert sand are pretreated separately; The pretreatment of steel slag includes: taking converter steel slag produced by Xinjiang Bayi Steel Plant, screening it using a vibrating screen (screen size 4.75mm), taking the undersize material, and sending the undersize steel slag into a drum-type stone washing machine, rinsing it with clean water for 5-10 minutes to remove surface adhering substances; sending the washed steel slag into a dryer, drying it at 105℃±5℃ to constant weight (moisture content <1%), and setting it aside for later use.
[0041] The pretreatment of desert sand includes: taking Taklamakan desert sand, screening it through a 4.75mm square hole sieve to remove excessively large impurities, and obtaining pretreated desert sand; The free calcium oxide content in the steel slag was tested according to YB / T 4328-2012, and the result was 2.1%; the autoclaving pulverization rate of the steel slag was tested according to GB / T 24175, and the result was 1.8%, which meets the stability requirements for steel slag used in construction. Step S2, Volume ratio calculation: Based on the apparent density of desert sand 2440 kg / m³ 3 Bulk density 1530 kg / m³3 The apparent density of steel slag is 3350 kg / m³. 3 Bulk density 2170 kg / m³ 3 The volume ratio of steel slag to desert sand was determined to be 1:3.
[0042] Step S3, Mixing and blending: Accurately weigh 400L of pretreated dried steel slag (approximately 868kg) and 1200L of pretreated desert sand (approximately 1836kg), put them into a 2m³ capacity forced mixer, set the speed to medium-high speed, and continuously dry mix for 6 minutes until the color is uniform and there is no visible layering. Step S4, Performance Testing: The composite sand obtained in step S3 was sampled and tested according to national standards. The results are shown in Table 3.
[0043] Example 3 A process for preparing corrosion-resistant steel slag desert sand composite sand includes the following steps: Step S1, Raw material pretreatment: Steel slag and desert sand are pretreated separately; The pretreatment of steel slag includes: taking converter steel slag produced by Xinjiang Bayi Steel Plant, screening it using a vibrating screen (screen size 4.75mm), taking the undersize material, and sending the undersize steel slag into a drum-type stone washing machine, rinsing it with clean water for 5-10 minutes to remove surface adhering substances; sending the washed steel slag into a dryer, drying it at 105℃±5℃ to constant weight (moisture content <1%), and setting it aside for later use.
[0044] The pretreatment of desert sand includes: taking Taklamakan desert sand, screening it through a 4.75mm square hole sieve to remove excessively large impurities, and obtaining pretreated desert sand; The free calcium oxide content in the steel slag was tested according to YB / T 4328-2012, and the result was 2.1%; the autoclaving pulverization rate of the steel slag was tested according to GB / T 24175, and the result was 1.8%, which meets the stability requirements for steel slag used in construction. Step S2, Volume ratio calculation: Based on the apparent density of desert sand 2440 kg / m³ 3 Bulk density 1530 kg / m³ 3 The apparent density of steel slag is 3350 kg / m³. 3 Bulk density 2170 kg / m³ 3 The volume ratio of steel slag to desert sand was determined to be 1:1.5.
[0045] Step S3, Mixing and blending: Accurately weigh 600L of pretreated dried steel slag (approximately 1302kg) and 900L of pretreated desert sand (approximately 1377kg), put them into a 2m³ capacity forced mixer, set the speed to medium-high speed, and continuously dry mix for 8 minutes until the color is uniform and there is no visible layering. Step S4, Performance Testing: The composite sand obtained in step S3 was sampled and tested according to national standards. The results are shown in Table 3.
[0046] Comparative Example 1 The sand used was pretreated Taklamakan Desert sand that had undergone 4.75mm sieve screening, without the addition of any steel slag or compounding. The remaining pretreatment and testing conditions were the same as in Example 1, and the results are shown in Table 3.
[0047] Comparative Example 2 Commercially available ordinary limestone manufactured sand (fineness modulus 2.8, meeting the requirements of GB / T 14684-2022 Zone II medium sand) was selected without any modification treatment and sampled and tested according to national standards. The results are shown in Table 3.
[0048] IV. Results and Analysis Table 3 Summary of Test Results
[0049] Results analysis: (1) Fineness modulus and particle size distribution analysis The fineness modulus of Comparative Example 1 was only 1.2, which belongs to Zone III fine sand in GB / T 14684-2022, far below the requirement of 2.3-3.0 for medium sand used in engineering, and therefore cannot be directly used in concrete preparation. This verifies the technical defects of "extremely uneven gradation and excessively high fine particle content of desert sand" pointed out in the background technology.
[0050] In contrast, Examples 1-3, by combining steel slag and desert sand at different volume ratios, achieved fineness moduli of 2.6, 2.4 and 2.8 respectively, all falling within the target range of 2.3-3.0. The particle size distribution met the requirements for medium sand in Zone II, indicating that the present invention can accurately control the fineness modulus of composite sand within the optimal range for engineering sand through simple volume ratio adjustment.
[0051] Among them, Example 3 had the highest fineness modulus, while Example 2 had the lowest. This indicates that the higher the proportion of steel slag, the larger the fineness modulus of the composite sand. This rule provides a technical basis for flexibly adjusting the fineness modulus according to engineering needs.
[0052] Although Comparative Example 2 has a fineness modulus of 2.8 and a qualified gradation, its source is natural rock crushing, which does not involve the resource utilization of solid waste and does not have corrosion resistance.
[0053] (2) Bulk density analysis The bulk density of pure desert sand is only 1530 kg / m³. 3 It has high porosity and low density. The bulk density of Examples 1-3 reached 1850 kg / m³, respectively.3 1780kg / m 3 and 1890kg / m 3 Compared with pure desert sand, the density of the composite sand increased by 20.9%, 16.3%, and 23.5%, respectively. This indicates that the coarse steel slag particles effectively filled the gaps between the fine desert sand particles, achieving synergistic complementarity between coarse and fine gradations and significantly improving the density of the composite sand.
[0054] Example 3 showed the highest bulk density, while Example 2 showed the lowest bulk density, further verifying the contribution of steel slag to increasing bulk density.
[0055] The bulk density of ordinary manufactured sand is 1680 kg / m³ 3 Although it is higher than that of pure desert sand, it is still lower than that of the embodiments of the present invention, indicating that the composite sand of the present invention has an advantage in terms of density.
[0056] (3) Corrosion resistance analysis After being soaked in 5% Na2SO4 solution for 28 days, the mass loss rate of pure desert sand was 4.0%, indicating that its resistance to sulfate corrosion was poor. The mass loss rate of Comparative Example 2 was 3.5%, which was slightly better than that of pure desert sand, but still at a relatively high level.
[0057] The mass loss rates of Examples 1-3 were 1.6%, 2.4%, and 1.3%, respectively, which were 60%, 40%, and 67.5% lower than those of pure desert sand. This significant improvement stems from the chemical corrosion resistance of the steel slag itself—the high CaO, SiO2, and Fe2O3 content in the steel slag gives it better chemical stability in sulfate environments.
[0058] It is worth noting that Example 3 exhibited the best corrosion resistance, while Example 2 showed relatively weaker corrosion resistance, indicating a positive correlation between the amount of steel slag added and the corrosion resistance of the composite sand. This provides a basis for selecting appropriate proportions for different corrosive environments.
[0059] Although Comparative Example 2 met the fineness modulus requirements, its mass loss rate was 3.5%, only 12.5% lower than that of pure desert sand, far lower than that of the embodiments of the present invention. This indicates that while conventional manufactured sand can meet the gradation requirements, it cannot solve the corrosion resistance problem, further highlighting the irreplaceable nature of the "steel slag + desert sand" synergistic solution of the present invention in terms of corrosion resistance.
[0060] (4) Stability analysis of steel slag The free calcium oxide content of the steel slag used in Examples 1-3 was 2.1%, and the autoclaving pulverization rate was 1.8%, both meeting the relevant standard requirements. This proves that the converter steel slag selected in this invention has good volume stability after pretreatment and will not cause expansion and damage risks to the long-term use of composite sand, eliminating the technical concerns of those skilled in the art about the potential for poor volume stability when using steel slag as aggregate.
[0061] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A process for preparing corrosion-resistant steel slag desert sand composite sand, characterized in that, Includes the following steps: Step S1, Raw material pretreatment: Steel slag and desert sand are pretreated separately; The pretreatment of steel slag includes: screening the steel slag raw material to ensure that it all passes through a 4.75mm sieve, followed by washing and drying. The pretreatment of desert sand includes: screening the desert sand raw material so that all of it passes through a 4.75mm sieve; Step S2, Volume ratio calculation: Based on the physical property parameters of steel slag and desert sand, calculate the volume mixing ratio of steel slag and desert sand required to make the fineness modulus of the final composite sand fall within the range of 2.3 to 3.0; Step S3, Mixing and blending: According to the volume ratio calculated in step S2, the pretreated steel slag and desert sand are dry and uniformly mixed to obtain the corrosion-resistant steel slag and desert sand composite sand. Step S4, Performance Testing: The composite sand obtained in Step S3 is sampled and tested according to national standards. The test indicators include fineness modulus, mud content, bulk density, alkali activity and corrosion resistance, ensuring that its fineness modulus is between 2.3 and 3.0 and that the other indicators meet the requirements for engineering sand.
2. The process for preparing corrosion-resistant steel slag desert sand composite sand according to claim 1, characterized in that, The desert sand in question is from the Taklamakan Desert, and its apparent density is 2440 kg / m³. 3 The bulk density is 1530 kg / m³ 3 ; The particle size distribution characteristics are: cumulative residue on a 0.075 mm sieve greater than 95%, and cumulative residue on a 0.15 mm sieve greater than 80%. The apparent density of the steel slag is 3350 kg / m³. 3 The bulk density is 2170 kg / m³ 3 .
3. The process for preparing corrosion-resistant steel slag desert sand composite sand according to claim 1, characterized in that, After screening, the steel slag is mainly distributed in the range of 2.36 mm, 1.18 mm and 0.6 mm sieve apertures, and the particles that pass through the 4.75 mm sieve and are distributed in the range of 1.18-4.75 mm account for the majority of the mass.
4. The process for preparing corrosion-resistant steel slag desert sand composite sand according to claim 1, characterized in that, The volume ratio of steel slag to desert sand in step S2 ranges from 1:1 to 1:
3.
5. The process for preparing corrosion-resistant steel slag desert sand composite sand according to claim 1, characterized in that, The moisture content at the end of the drying process in step S1 is less than 1%; the dry uniform mixing in step S3 is carried out using a forced mixer or a zero-gravity mixer, and the mixing time is not less than 5 minutes.
6. The process for preparing corrosion-resistant steel slag desert sand composite sand according to claim 1, characterized in that, The steel slag is converter steel slag, whose main chemical composition includes CaO 40%-50%, SiO2 15%-20%, and Fe2O3 15%-25%. The steel slag is tested for free calcium oxide content before pretreatment to ensure that its volume stability meets the standard requirements for steel slag used in construction.
7. A corrosion-resistant steel slag desert sand composite sand, prepared by the blending process described in any one of claims 1-6, having a fineness modulus of 2.3-3.0, a particle size distribution that meets the requirements of Class II medium sand for construction sand in national standard GB / T 14684, and having better corrosion resistance than pure desert sand.
8. The corrosion-resistant steel slag desert sand composite sand according to claim 7, characterized in that, The composite sand exhibits a mass loss rate at least 40% lower than that of pure desert sand in the sulfate erosion test, which employs the Na2SO4 solution immersion method.
9. The corrosion-resistant steel slag desert sand composite sand according to claim 7, characterized in that, The bulk density of the composite sand is greater than that of pure desert sand, and its mud content, alkali activity, and content of harmful substances all comply with the provisions of national standard GB / T 14684.
Citation Information
Patent Citations
A composite sand concrete
CN111662058B
Permeable brick prepared with steel slag and desert sand
CN202989718U